Distribution of GPs in Scotland by age, gender and deprivation. Issue 4 (November 2015) - Blane, David N; McLean, Gary; Watt, Graham
General practice in the UK is widely reported to be in crisis, with particular concerns about recruitment and retention of family doctors. This study assessed the distribution of GPs in Scotland by age, gender and deprivation, using routinely available data. We found that there are more GPs (and fewer patients per GP) in the least deprived deciles than there are in the most deprived deciles. Furthermore, there are a higher proportion of older GPs in the most deprived deciles. There are also important gender differences in the distribution of GPs. We discuss the implications of these findings for policymakers and practitioners.